The study of myocardial ischemia-reperfusion treatment through computational modelling. (21st January 2021) - Wan Ab Naim, Wan Naimah; Mohamed Mokhtarudin, Mohd Jamil; Chan, Bee Ting; Lim, Einly; Ahmad Bakir, Azam; Nik Mohamed, Nik Abdullah
Highlights: The mechanism of ischemia-reperfusion treatment is studied using an oxygen model. Electro-oxygen model is used to observe the myocardial damage region. Oxygen exceeds 1.0 (optimum) at early reperfusion increases reperfusion-injury risk. Risk increases for the case of long ischemia-reperfusion time and >80% early oxygen. From its conductivity result, the injury region is limited within the ischemic area. Abstract: Reperfusion of the blood flow to ischemic myocardium is the standard treatment for patients suffering myocardial infarction. However, the reperfusion itself can also induce myocardial injury, in which the actual mechanism and its risk factors remain unclear. This work aims to study the mechanism of ischemia–reperfusion treatment using a three-dimensional (3D) oxygen diffusion model. An electrical model is then coupled to an oxygen model to identify the possible region of myocardial damage. Our findings show that the value of oxygen exceeds its optimum (>1.0) at the ischemic area during early reperfusion period. This complication was exacerbated in a longer ischemic period. While a longer reperfusion time causes a continuous excessive oxygen supply to the ischemic area throughout the reperfusion time. This work also suggests the use of less than 0.8 of initial oxygen concentration in the reperfusion treatment to prevent undesired upsurge at the early reperfusion period and further myocardial injury. We also found the region at risk for myocardial injury is confined in the ischemic vicinity revealed by its electrical conductivity impairment. Although there is a risk that reperfusion leads to myocardial injury for excessive oxygen accumulation, the reperfusion treatment is helpful in reducing the infarct size.